2008
DOI: 10.1159/000165355
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Lesion Subtypes and Cognitive Deficits in Patients with Memory Impairment

Abstract: Aim: To analyze the relationship between periventricular (PV) and subcortical (SC) white matter lesions (WML) and cognitive function in patients with memory impairment. Methods: In total, 253 patients with Global Deterioration Scale scores ≧3 who had been referred to a university-based memory unit due to memory complaints were included (mean age 69.7 years, 124 females). Cognitive function was assessed with the Mini-Mental State Examination (MMSE) and the Neurobehavioral Cognitive Status Examination (Cognistat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
3
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 60 publications
(43 reference statements)
6
18
3
4
Order By: Relevance
“…These aspects pertained chiefly to executive function. Similar findings have been obtained in cross-sectional and longitudinal studies of older patients and symptomatic individuals [2,4,6,7,35,36]. Some studies suggested an association of WMLs with a faster decline in global cognitive performance, executive function, and processing speed [2,37,38].…”
Section: Discussionsupporting
confidence: 80%
“…These aspects pertained chiefly to executive function. Similar findings have been obtained in cross-sectional and longitudinal studies of older patients and symptomatic individuals [2,4,6,7,35,36]. Some studies suggested an association of WMLs with a faster decline in global cognitive performance, executive function, and processing speed [2,37,38].…”
Section: Discussionsupporting
confidence: 80%
“…Some authors reported that WMLs were related to impaired global cognitive function or neuropsychologic performance in AD patients, whereas others failed to show significant differences in cognitive function among AD patients with and without WMLs [8][9][10][11][12]. These discrepancies may be due to differences in the study samples or methods used to assess cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although differences are not found in neuropsychological test scores in comparison with a 'healthy' group, some neuroimaging studies in people with SMC showed a smaller entorhinal cortex (Jessen et al 2006), a reduced hippocampal volume (Van der Flier et al 2004), reduced metabolism (Mosconi et al 2008) and subcortical parieto-occipital white matter lesions (Stenset et al 2008). Studies of brain activity during cognitive tasks note that subjects with SMC present an increase in activity in comparison with the control group (Rodda et al 2009;Rodda et al 2010;Maestu et al 2010;Jessen et al 2010;Elfgren et al 2010;Gallassi et al 2010;Benito-León et al 2010;Luck et al 2010).…”
Section: Introductionmentioning
confidence: 97%